The Rate of Exclusive Breastfeeding Success on Working Mothers in Klaten Regency - Kholifa Nur Ardhina; Miranti Dewi Pramaningtyas; Emi Azmi Choironi (Jurnal Surya Medika (JSM), 2020)
Work is often the reason for mothers not to have the opportunity to give exclusively breastfeeding for 6 months to their babies. This reason is motivated by the lack of sufficient time to breastfeed or express milk. This is also experienced by breastfeeding mothers in the Klaten region who already have regulations on exclusive breastfeeding. This study aims to determine the large percentage of exclusive breastfeeding for working mothers in Klaten district. This study uses a categorical descriptive method involving 117 respondents. Primary data were collected from the midwife clinics of Ni'ma and Warsiti, the Belang Wetan posyandu, and several TKs in Klaten, which were included in the inclusion criteria. A total of 63 mothers (54%) who worked successfully gave exclusive breastfeeding to their children, while unsuccessful were 54 mothers (46%). The success rate of exclusive breastfeeding in the age group of 17-25 years was 14 subjects (11.97%), at the age of 26-35 years was 44 (37.61%) and at the age of 36-45 was 5 (4.27%). The educational background of successful working mothers is D4 / S1 of 21 subjects (17.95%). The occupational groups that succeeded in providing exclusive breastfeeding were Teachers (54.5%), Entrepreneurs (75%), Civil Servants (80%), BUMN Employees (66.7%), and Health Workers (90.9%). The percentage of success of exclusive breastfeeding for mothers who worked for ≤ 8 hours amounted to 57.1%, while mothers who worked> 8 hours amounted to 36.8%. The higher the level of mother's education, the higher the success rate of exclusive breastfeeding. The longer the mother works, the lower the success rate of exclusive breastfeeding.